High technology and the competition state : an analysis of the ureka initiative - Peterson, John, 1958- (London ; New York : Routledge, 1993)
This book is about: High technology and the competition state; Partners, process; and projects; ...
Keywords: Technology; EUREKA Organization; EUREKA Organization; Research, Industrial -- Europe; High technology industries -- Europe; Technology and state -- Europe